Formulasi Tablet Effervescent Ekstrak Sirih Cina (Peperomia pellucida L.) Dan Uji Aktivitas Terhadap Antibakteri Staphylococcus aureus - Vinsensia Ivana Widjayanti; Iwan Setiawan (Universitas Muhammadiyah Surakarta, 2022)
Chinese Betel herb (Peperomia pellucida L.) has flavonoid and saponin content compounds that can inhibit bacterial growth. The innovation of effervescent tablets used as disinfectants is not widely known in the Indonesian market. This preparation has the advantage of being easy to manufacture as a disinfectant. Chinese betel herb extract is formulated into an effervescent tablet preparation. This study aims to determine the influence on variations in the levels of binders and fillers in the physical properties of effervescent tablet preparations and determine the activity in the effervescent tablet formula of Chinese betel extract (Peperomia pellucida L.) in inhibiting the growth of Staphylococcus aureus bacteria. Chinese betel herb extract is obtained through a maceration extraction process using methanol solvent for 5 days. The preparation of effervescent tablets is made 3 formulas, namely the concentration of binding substances 10%, 13%, 15%. Physical tests of tablet preparations include organoleptic tests, tablet hardness tests, tablet soluble time tests, size uniformity tests, weight uniformity tests,, fragility tests and antibacterial activity tests against Staphylococcus aureus with disc paper diffusion methods.The best formula tablets are formula I (PEG 10%) with uniformity of weight 525±17,014, tablet hardness 3,452±1,172, tablet fragility 0.264%, soluble time 1 minute 6 seconds, uniformity size 3.33±0.06. The results of antibacterial activity tests showed weak inhibitory power with an average formula value of 4.51±0.02.